Differntial Fecundity, Markets, and Gender Roles - Siow, Aloysius (Journal of Political Economy, 1998)
Women are fecund for a shorter period of their lives than men. This paper investigates how differential fecundity interacts with marriage, labor, and financial markets to affect gender roles. The main findings of the paper are as follows: (i) Fecund women are relatively scarce. Men will behave differently than women in response to this scarcity. In the most fundamental way, demand and supply conditions in the marriage market affect gender roles. (ii) Differential fecundity does not have any market‐invariant gender effect. Gender roles depend on the way in which marriage, labor, and financial markets interact. (iii) Gender differences in the labor market can occur without corresponding differences in labor market opportunities, productivities in child rearing, or social norms. (iv) With uncertainty in human capital accumulation and no insurance against this uncertainty, the model's predictions are consistent with observed gender roles.